2021
DOI: 10.3389/fpsyg.2021.774472
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Internal Structure, Psychometric Properties, and Measurement Invariance of the Work-Related Rumination Scale – Spanish Version

Abstract: Background: The aim of the current study was to examine the internal structure and assess the psychometric properties of the Work-Related Rumination Scale (WRRS) – Spanish version in a Puerto Rican sample of workers. This instrument is a 15-item questionnaire, which has three factors, affective rumination, problem-solving pondering, and detachment. This measure is used in the occupational health psychology context; however, there is little evidence of its psychometric properties.Materials and Methods: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 108 publications
(150 reference statements)
2
10
0
Order By: Relevance
“…In this study, we used the ULSMV estimator to test a three-dimension model, with χ 2 = 659.871 (87), Z = 22.617, p < 0.001, CFI = 0.880, uSRMR = 0.068 [90% CI, 0.067-0.070], and RMSEA = 0.131 [0.121-0.140] without item 13 because we obtained a low, negative, and non-significant factor loading (λ = −0.091) and some studies in Latin America have suggested that some items of MBI-GS are problematic [e.g., (50,51)]. Specifically, item 13 has been shown to have some factorial complexity in a study conducted in Puerto Rico with a sample of Puerto Rican employees (52). Meanwhile, reliability was estimated for the three subscales, i.e., exhaustion, cynicism, and professional efficacy, using alpha and omega with their respective 90% confidence intervals.…”
Section: Burnoutmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, we used the ULSMV estimator to test a three-dimension model, with χ 2 = 659.871 (87), Z = 22.617, p < 0.001, CFI = 0.880, uSRMR = 0.068 [90% CI, 0.067-0.070], and RMSEA = 0.131 [0.121-0.140] without item 13 because we obtained a low, negative, and non-significant factor loading (λ = −0.091) and some studies in Latin America have suggested that some items of MBI-GS are problematic [e.g., (50,51)]. Specifically, item 13 has been shown to have some factorial complexity in a study conducted in Puerto Rico with a sample of Puerto Rican employees (52). Meanwhile, reliability was estimated for the three subscales, i.e., exhaustion, cynicism, and professional efficacy, using alpha and omega with their respective 90% confidence intervals.…”
Section: Burnoutmentioning
confidence: 72%
“…Another possible factor that affected the relationship between depression and burnout could be related to the poor fit of the MBI-GS in this sample. Thus, this is another factor that needs to be examined in the future despite the fact that a study (52) with a sample of Puerto Rican workers obtained excellent fit indices although they used the exploratory structural equation modeling (ESEM) in their study, which allows cross-loadings and the fit indices tend to become better.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…The degree of equality of the factorial loadings of the items is frequently connected with this distance, a condition known as tau-equivalence to validate the coefficient (Green & Yang, 2009;Hayes & Coutts, 2020). This closeness implies that the assessment of internal consistency may be done well with the coefficient, without the need for SEM modeling or SEM modeling methodologies to estimate the coefficient (Rosario-Hernández et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using Cronbach's alpha techniques, the reliability of the UWES and its subscales has been reported between .82 to .93 (Schaufeli & Bakker, 2003). Several studies carried out in Puerto Rico have used it with samples of employed people, and its results support the internal structure, and its reliability coefficients fluctuated between .81 to .95 using the Cronbach alpha and omega technique (e.g., Martínez-Alvarado et al, 2017;Rodríguez Montalban et al, 2011;Rosario-Hernández et al, 2021). For the current study, we used the UWES short form, which comprises nine items, three items for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The Work-Related Rumination Questionnaire (WRRQ; Cropley et al, 2012) is a widely used measure to assess workrelated cognition via affective rumination, problem-solving pondering and (lack of) detachment. It has been translated into different languages (Firoozabadi et al, 2018;Sulak-Akyüz and Sulak, 2019;Rosario-Hernández et al, 2021;Pauli and Lang, 2021b;Lin and Bai, 2022) and utilized to compare measurements across different groups of employees (e.g., Pravettoni et al, 2007;Pauli and Lang, 2021a) or over time (Hamesch et al, 2014;Syrek et al, 2017;Kinnunen et al, 2019). However, it has yet to be established whether different measurement outcomes are attributable to actual differences between groups instead of differences in the measurement attributes (Steinmetz, 2013).…”
Section: Introductionmentioning
confidence: 99%